2018
DOI: 10.1016/j.biopsych.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 Receptor–Positive Neurons in the Lateral Nucleus of the Cerebellum Contribute to Cognitive Behavior

Abstract: Collectively, these data demonstrate a functional link between genetically distinct neurons in the LCN and cognitive behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 106 publications
4
75
0
Order By: Relevance
“…It is not only the higher cortical areas where DREADDs have been applied to study DA-regulated cognition. The importance of D 1 Rs located in the lateral nucleus of the cerebellum was demonstrated using hM4Di-mediated cerebellar stimulation in D 1 R-Cre mice to induce deficits on working memory and prepulse inhibition of the acoustic startle response (Locke et al, 2018).…”
mentioning
confidence: 99%
“…It is not only the higher cortical areas where DREADDs have been applied to study DA-regulated cognition. The importance of D 1 Rs located in the lateral nucleus of the cerebellum was demonstrated using hM4Di-mediated cerebellar stimulation in D 1 R-Cre mice to induce deficits on working memory and prepulse inhibition of the acoustic startle response (Locke et al, 2018).…”
mentioning
confidence: 99%
“…This neurotransmitter participates integrally in cellular signaling, which has a favorable effect on LTP in the hippocampus, striatum and amygdala (Baldwin, Sadeghian, & Kelley, ;). It has been described that dopamine promotes the processes of acquisition and storage of information during LTP, through the activation of D1 receptors (Granado et al, ; Lisman & Grace, ; Locke et al, ). Particularly, it has been demonstrated that gene inactivation of the D1 receptor (D1R –/–) in mice reduces the early (E–) and late (L–) phase of LTP in the CA1 region of the hippocampus, a critical brain region for the LTP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PC-D2R-cKO mice had performance similar to control mice in accelerating rotarod, beam walking and coat-hanger tests, further indicating that motor routines and coordination were not altered in D2R-cKO ( Figures S8b-d). In addition to its role in movement control, the cerebellum also takes part in cognitive abilities, regulation of emotions and social interactions 5,6 . We therefore tested whether D2R deletion from PCs might alter social interactions using the 3-chamber test 44 .…”
Section: D2r Expressed In Purkinje Cells Regulate Preference For Socimentioning
confidence: 99%
“…The cerebellum is a brain area that has long been considered to be solely involved in coordination of voluntary movements including the control of posture, balance and gaze orientation 1,2 . However, increasing evidence indicates that the cerebellum also takes part in cognitive and emotional abilities as well as social interactions [3][4][5][6] . The control of these various components of motor, cognitive and affective behaviors is largely ascribed to its modular compartmentalization into functional independent units tightly modulated by monoaminergic inputs which signal arousal, salience and valence [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%